Референтен модел за рангирање на нивото на имплементација на системите за безбедност и здравје при работа - Велковски, Трајче (Машински факултет, УКИМ, Скопје, 2019)
The European Union's regulations on safety and health at work originate from the European Framework Directive 89/391 / EEC (Council Directive of 12 June 1989), in which the main aim is to introduce preventive measures that will promote awareness through specific activities for enhancing the occupational safety and health of employees in the workplace, guided by general principles for prevention of the occupational risks. The Constitution of the Republic of North Macedonia, in particular Article 32, paragraph 1 clearly states that "Everyone has the right to work, free choice of employment, safety at work and material security during temporary unemployment". The main purpose of the doctoral dissertation research is the creation of a reference model for ranking the level of implementation of occupational safety and health systems. The purpose of this model is to give the opportunity of benchmarking between the legal entities on the occupational safety and health and to enable the development of a new approach with the ultimate goal of contribution to reducing workplace accidents. The final result, the created model, contribute for reducing the lost working time of the legal entity as a result of occupational injuries and increases the employee productivity and competitive advantage through continuous improvement. The conceptual model is developed on the base of an analysis of existing scientific and research literature and OSH legislation in RNM. Amodel containing 50 risk indicators, divided into 14 groups is developed, with the application of the Delphi method and reaching the consensus of 32 experts. Each indicator is defined by a weight factor rated by the panel of experts on the base of its impact on reducing the time lost by the occupational injuries. In the verification process the model is verified through its application in a statistically relevant sample of large companies in manufacturing industry, with quantified results for the level of implementation of their occupational safety and health systems.
Reference rating model for the level of implementation of the occupational safety and health systems
Докторска дисертација одбранета во 2019 година на Машинскиот факултет во Скопје, под менторство на проф. д–р Јасмина Чаловска.
Keywords: occupational safety and health, performance measurement, occupational safety and health management systems, occupational injuries